A Novel Hydrophilic Membrane based on PAA-coated Cellulose Acetate-chitosan for PAHs Pollutant Removal - Syahrir, Muhammad; Danial, Muhammad; Alam, Muhammad Nur; Irfandi, Rizal; Putri, Suriati Eka; Nururrahmah, Nururrahmah (Trends in Sciences, 2026)
The separation of Polycyclic Aromatic Hydrocarbons (PAHs) from wastewater is essential due to its mutagenic and carcinogenic properties. Cellulose acetate-chitosan membranes (CA-CS) coated with polyelectrolyte complex poly(acrylic-acid) (PAA) at various concentrations (100, 200, 500 and 1,000 ppm) have been synthesized to improve the separation performance of PAHs. Fourier Transform Infrared (FTIR) characterization confirms the formation of polyelectrolyte complex PAA-CS through NH₃⁺/COO⁻ ion pairs (strengthening of the bands 1,560 - 1,600 and 1,410 cm−1 and attenuation of C=O at 1,730 cm−1), while Scanning Electron Microscopy (SEM) analysis and surface contours show changes from a nodular surface of CA-CS membrane to a more homogeneous layer during the coating process. X-Ray diffraction patterns indicate structural regularity in the composition. The water contact angle decreased from 65.56° in CA-CS to 36.34° after PAA coating at 500 ppm, and the swelling index increased from 48.24% to 73.95% confirming the membrane’s hydrophilic nature after coating. Mechanically, tensile strength increased with increasing PAA concentration, due to physical cross-linking via hydrogen bonds that solidified the network. Membrane performance test showed that permeate flux and PAHs rejection increased after CA-CS coating and achieved the best performance at 500 ppm PAA across all operating pressures (2 - 8 bar) with an optimum flux of 11.56 L·m−2·h−1 and optimum PAHs rejection of > 90%. In addition, the CA-CS/PAA 500 membrane also showed the best antifouling properties with the lowest Flux Decline Ratio (FDR) of 20% and the highest Flux Recovery Ratio (FRR) of 78%. Ultimately, poly(acrylic acid)-coated cellulose acetate-chitosan biopolymer-based membranes have great potential for continuously and sustainably separating PAH pollutants from wastewater. HIGHLIGHTS The CA-CS membrane coated with a PAA complex polyelectrolyte offers anti-fouling properties, restoring flux to up to 78%, thereby providing benefits for long-term membrane use. This high anti-fouling property is due to the membrane’s superhydrophilic nature, which affects its ability to form a hydrated layer that provides a steric effect during filtration. In addition, the use of a cellulose acetate biopolymer combined with chitosan, then coated with a PAA complex polyelectrolyte and subsequently applied to the separation of PAH pollutants from wastewater, is the latest treasure in membrane technology studies, as far as the literature search has revealed. GRAPHICAL ABSTRACT